Influences of Online Education System on the Quality of Life of Children During the COVID-19 Pandemic Lockdown - An Evaluative Study - V Usha Kiran; Rajasekhar Vabbalareddi; Jayalakshmi Pandranki; V Bhavesh Nandan (Indian Journal of Dental Research)
Background: Conventional classroom learning took a beating during the COVID-19 lockdown. This was not the first time educational institutions had to shut down globally. Alternative teaching methods needed to be incorporated into the educational system, and therefore, it was prudent to study the effects of such novel teaching methods on the quality of life of children. The aim of the study was to evaluate factors affecting the general and oral health-related quality of life of children during online classes during the COVID-19 pandemic. Material and Methods: A digital questionnaire-based study was conducted among children aged nine to fourteen years who attended online classes during the COVID-19 lockdown. Pearson’s Chi-square test was used for comparative evaluation between variables. Results: A total of 182 children responded to the questionnaire. Among them 36.3% of children reported having headaches, 32.4% had eyestrain, 13.7% had watering eyes, 10% had back pain, 23.6% had neck pain, 14.8% complained of disturbed sleep and 6% had hearing disturbances during the phase of online classes. In addition, 32.4% of children had the habit of snacking between meals and 8.2% reported tooth pain. There was a statistically significant difference (P = 0.036) between the time spent per day attending online classes and the number of problems reported. Conclusions: Several factors have been identified that affected the children’s quality of life during their online classes. Increased screen time without maintaining ergonomics could lead to adverse effects. Also, children need to be educated about snacking habits and oral hygiene practices to achieve optimal oral health.